Dendritic and Synaptic Degeneration in Pyramidal Neurons of the Sensorimotor Cortex in Neonatal Mice With Kaolin-Induced Hydrocephalus - Omowumi M. Femi-Akinlosotu; Matthew T. Shokunbi; Matthew T. Shokunbi; Thajasvarie Naicker (Frontiers Media S.A., 2019)
Obstructive hydrocephalus is a brain disorder in which the circulation of cerebrospinal fluid (CSF) is altered in a manner that causes expansion of fluid-filled intracranial compartments particularly the ventricles. The pyramidal neurons of the sensorimotor cortex are excitatory in nature and their dendritic spines are targets of excitatory synapses. This study evaluated the effect of hydrocephalus on dendritic arborization and synaptic structure of the pyramidal neurons of the sensorimotor cortex of neonatal hydrocephalic mice. Sterile kaolin suspension (0.01 ml of 250 mg/mL) was injected intracisternally into day old mice. Control animals mice received sham injections. Pups were weighed and sacrificed on postnatal days (PND) 7, 14 and 21. Fixed brain tissue blocks were silver impregnated using a modified Golgi staining technique and immunolabeled with synaptophysin to determine dendritic morphology and synaptic integrity respectively. Data were analyzed using ANOVA at α0.05. Golgi staining revealed diminished arborization of the basal dendrites and loss of dendritic spines in the pyramidal neurons of hydrocephalic mice. Compared to age-matched controls, there was a significant reduction in the percentage immunoreactivity of anti-synaptophysin in hydrocephalic mice on PND 7 (14.26 ± 1.91% vs. 62.57 ± 9.40%), PND 14 (4.19 ± 1.57% vs. 93.01 ± 1.66%) and PND 21 (17.55 ± 2.76% vs. 99.11 ± 0.63%) respectively. These alterations suggest impaired neuronal connections that are essential for the development of cortical circuits and may be the structural basis of the neurobehavioral deficits observed in neonatal hydrocephalus.